Origem da vida e as tecnologias digitais de informação e comunicação - TDIC: uma proposta de sequência didática investigativa - Sebastião Lopes da Cruz (2022)
Contemporary society has been increasingly expanding the use of Digital Information and Communication Technologies (DICT), creating new ways of interaction and organization among people. In the educational field and with the students' interest in digital technologies, DICT can be used as tools capable of providing different ways of learning and transforming pedagogical practices. These digital tools have become so indispensable that the Common National Curricular Base (BNCC), which governs the elaboration of the Basic Education curriculum, has placed the digital world in a teaching competence that should cross the curriculum of all subjects, emphasizing its sensible and ethical use. In this perspective, the use of DICT associated with inquiry-based teaching, through projects integrated with curriculum content, can help transform school relations, enabling learners to develop autonomy and creativity, with research, information selection, and teamwork. In this context, an investigative didactic sequence is proposed in Biology teaching on the theme "Origin of Life", addressing theories of origin of species and biological evolution, as well as the difficulties and controversies faced by teachers and students when questioning this content, which is of great contribution to the conclusion of high school. The elucidation of the theme-problem through investigation and using the stages of the scientific process makes the student take all this organization to their daily lives beyond school, awakening in them critical thinking and protagonist. Another important point is the clear contextualization of the content, bringing into the classroom relationships that match the reality of the students. The dynamic developed, a conversation circle, allowed us to identify a knowledge fragmented by the students and permeated by beliefs, which was being overcome during the development of the sequence, by assimilation and interaction with new information and concepts presented within the theme. In this way, the students were able to dialogue and, above all, respect the scientific and ideological thoughts of each colleague. The use of "Kahoot" contributed to gamification in the classroom by allowing the use of the main elements of games such as establishing clear rules, immediate feedback, scoring for accuracy, competition between students/teams, and providing pleasure and fun during the teaching and learning process of the students. The results achieved regarding the students' performance in the evaluation and in the virtual educational game demonstrate a good understanding of the contents taught.